Pigmented Lesion of Buccal Mucosa - Manas Bajpai; Malay Kumar; Manish Kumar; Deshant Agarwal (Case Reports in Medicine)
Pigmented lesions are commonly found in the mouth. Such lesions represent a variety of clinical entities, ranging from physiologic changes to manifestation of systemic illness and malignant neoplasm. Diagnosis of such lesions requires a proper case history, extraoral and intraoral examination, and, in some cases, biopsy, aspiration cytology, and laboratory investigations. Here we present a case of purple lesion on the buccal mucosa of a 34-year-old male patient which was provisionally diagnosed as mucocele but on the basis of histopathological picture it was finally diagnosed as angiofibroma, and we also discuss the clinical and histopathological differential diagnosis.